PROCESS TOMOGRAPHY - AHMAD FUAD, FAZIATUL ALHANA (Universiti Teknologi PETRONAS, 2007)
In order to improve the design and control of Process Tomography, the project is presented in this study. Process tomography is a process of measuring electrical signals by using specific types of sensor. The sensors are arranged around an object, such as vessels or pipelines, to examine the internal characteristics of the subject. The information on the nature of the subject is obtained by reconstructing the measurements from the sensors into a 2-D or 3-D image. There are many methods that can be applied in process tomography. This includes optical tomography, resistive tomography, and acoustic tomography. The method used for this study is Electrical Impedance Tomography (EIT). EIT is a tomographic imaging method which enables the internal impedance ofanobject tobeimaged with the use of a ring of external electrodes. The author had done researches and studies regarding Process Tomography and EIT to obtain information of the process. The hardware part of the system consists of the sensor for the signal andthe impedance measurement circuit of the process tomography. Meanwhile, the software part includes the MATLAB program which is used for reconstructs the signals and displays the results. In this project, the author concentrates on the hardware circuit design and data acquisition system for EIT.